(untitled) (International Journal of Irrigation and Water Management, 2011)
Agricultural soils irrigated with wastewater pose a significant risk in the accumulation of heavy metals, a problem that affects agriculture and human health. An investigation was conducted on the concentration of heavy metals in agricultural soils and wastewater used for irrigation in plots of Mixquiahuala, Hidalgo. It analyzed the potential of hydrogen (pH), electrical conductivity (EC) and total extractable heavy metals in water and soil: As, Cd, Cr, Hg, Ni, Pb and Zn. Heavy metals were determined by using an Inductively Coupled Plasma (ICP) Perkin Elmer Optima 5300 (Inductively Coupled Plasma), using the methods recommended by the EPA (Environmental Protection Agency) and APHA (American Public Health Association). The study was conducted in November 2009. The sampling was conducted in two replications for both soils and wastewater. It compared the concentration of heavy metals with the criterion of Norma Oficial Mexicana-001-ECOL-1996. Based on these results, the concentration of extractable metals in agricultural soils of Mixquiahuala, Hidalgo, was presented in the following order: Pb > Ni > Cd > As > Cr > Hg. Water for agricultural irrigation did not present problems for use based on the concentration of As, Cd, Hg, Ni, Cr and Zn. However, lead concentration exceeded the maximum permissible limits in 40% of water samples analyzed. Considering the limits established in Spain, the concentrations of As, Ni and Cd exceeded permissible levels in 20, 60 and 60% respectively, of the samples analyzed.